2018
DOI: 10.1038/s41398-018-0130-x
|View full text |Cite
|
Sign up to set email alerts
|

Association and cis-mQTL analysis of variants in CHRNA3-A5, CHRNA7, CHRNB2, and CHRNB4 in relation to nicotine dependence in a Chinese Han population

Abstract: Nicotine dependence (ND) is a worldwide health problem. Numerous genetic studies have demonstrated a significant association of variants in nicotinic acetylcholine receptors (nAChRs) with smoking behaviors. However, most of these studies enrolled only subjects of European or African ancestry. In addition, although an increasing body of evidence implies a causal connection of single-nucleotide polymorphisms (SNPs) and epigenetic regulation of gene expression, few studies of this issue have been reported. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 60 publications
(57 reference statements)
0
13
0
Order By: Relevance
“…By using a dataset with all CHRNA5 methylation, expression, and risk of SNPs data available, Hancock et al first revealed that several genetic variations underlying CHRNA5 methylation in the human brain contributed to the risk of ND 60 . Recently, we linked SNP, cis -mQTL, and cis -eQTL 45 and revealed two methylated sites associated significantly with three SNPs forming four significant CpG–SNP pairs in a Chinese Han population. In the present study, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…By using a dataset with all CHRNA5 methylation, expression, and risk of SNPs data available, Hancock et al first revealed that several genetic variations underlying CHRNA5 methylation in the human brain contributed to the risk of ND 60 . Recently, we linked SNP, cis -mQTL, and cis -eQTL 45 and revealed two methylated sites associated significantly with three SNPs forming four significant CpG–SNP pairs in a Chinese Han population. In the present study, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The threshold for the genotyping rate of all SNPs was set as ≥95%, and the p value for the HWE was set as no ≥5%. All procedures and conditions used in this study were essentially the same as what we reported previously on the same samples 44 , 45 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To replicate the GWAS associations, 1,329 participants including 805 smokers and 524 nonsmokers were recruited from local hospitals in Jincheng and Taiyuan of Shanxi Province in China during 2012-2013 (12). All 1,329 participants were males, aged 19-62 years (Supplementary Table 1).…”
Section: Replication Analysismentioning
confidence: 99%